Codification of Islamic Law in the Muslim world: Political intrusion and professional Egoism - Zakariyah, Luqman (Islamic Cultural Centre London, 2017)
In the last century, the claim that the idea of codifying Islamic law is foreign, innovative and meant to undermine the divinity of the Islamic was promulgated by some Muslim jurists, including members of the Saudi Council of Senior Scholars (Hay’at Kibār al-‛Ulamā’). However, historically, the literature of Islamic legal theory reveals that the idea of codification of law, as understood in the West, is very close to the idea of codification of Islamic legal maxims (taqnīn al-qawā‛id al-fiqhiyyah) which unofficially emerged in Islamic jurisprudence as early as the first century of Islamic law. This paper aims to explore the historical concept of codification of Islamic law with a focus on political desiderata surrounding the calls for and against the concept of codification of Islamic law in Saudi Arabia with reference to other Muslim countries. It also suggests the concept of maṣlaḥa (public interest) and talfīq bayn al-madhāhib (hybridization of schools of jurisprudence) as justifications for the realization of the benefit of the concept. In order to preserve the sacred nature of Sharia while codifying its laws, this paper suggests some approaches to reconcile the opposing and supporting views of the codification. The paper concludes that codification of Islamic law is not a heretic or innovative concept in Islam, but rather it supports the foundation of Islamic law that is based on justice. The problem of codification of Islamic law only arises when there is lack of mechanisms in place.